Investigating the Effect of Matrices and Densities on the Efficiency of HPGe Gamma Spectroscopy Using MCNP - Loan, Truong Thi Hong; Phuong, Dang Nguyen; Phong, Do Pham Huu; Khanh, Tran Ai (Communications in Physics, 2009)
When determining radioactivities in environmental samples using low-level gamma spectroscopy, in order to raise detection limit, voluminous samples are used. It takes in account for the self-absorption (self-attenuation) of gamma rays in samples. The self-absorption effect is small or large depend on the sample shapes, matrices and densities. In this paper, we investigated the effect of some regular matrices such as water, soil, epoxy resin on the detector efficiency. Some analytical formulas for the correction of matrix and densities for soil sample was established and applied to calculate some activities from standard sample of IAEA-375.